The Chorus of User Voices: Meeting the Challenge of Patient-Reported Outcomes From Medications. (November 2017) - Nickman, Nancy A.
Prescription medication management by both healthcare providers and patients describe struggles not to inflict harm and encourage safe use in the context of culture and social relationships. Risk vs benefit assessments conducted in these contexts are essential for understanding how medication-taking decisions are made. Qualitatively-based Patient Reported Outcomes (PROs) are critical to understanding how medication pathways are navigated by both healthcare providers and patients seeking relief from maladies. Qualitative PROs have the potential to improve understanding of social and cultural factors that impact patient decision making whether to take a drug at all and would also serve to support developing models of patient-centered care.